ՓՐԿԱՐԱՐԱԿԱՆ ԾԱՌԱՅՈՒԹՅԱՆ ՍՊԱՅԻ ՀԱՏԿԱՆԻՇՆԵՐԻ ՁԵՎԱՎՈՐՄԱՆ ՀԱՅԵՑԱԿԱՐԳԱՅԻՆ ՀԱՐՑԵՐ - Matevosyan, Hamlet; Hayrapetyan, Armine; Gharibyan, Haykandukht; Gspoyan, Grisha; Amirkhanyan, Hasmik; Nazaryan, Lilit (Crisis Management and Technologies, 2023)
The purpose of the article is to present a number of conceptual issues of the formation of characteristics of the officer of the modern rescue service, including the set of knowledge, abilities, skills and norms of behavior that are necessary for the officer as a leader to effectively perform his functions, especially the functions and methods of self-management in team work, knowledge and ability to apply them. The set of characteristics is discussed from the juridical, ideological and linguistic points of view, trying to outline the way of formation of an officer.